Deep Learning for Venomous and Non-Venomous Snakes Classification - Yakubu Abubakar Lidani; Abdullahi Musa Yola; Abu Tasiu; Nura Muhammad Sani; Sulaiman Muhammad Gidado (PT. Teknologi Futuristik Indonesia, 2026)
Snakes are a major health threat in various communities, specifically where human and snake encounters are frequent. When a snake is not identified correctly, healthcare providers often administer the wrong treatment, this can worsen patient recovery outcomes or even prove fatal to the victim. Therefore, a fast, proper and accurate distinction between venomous and nonvenomous snakes is vital for proper antivenom administration. This study proposes a hybrid deep learning system combining a CNN and an LSTM model for snake image classification through feature extraction from visual data. The CNN extracts key spatial features such as colour and scale patterns, texture, and body shape, whereas the LSTM captures sequential dependencies across these features, by helping distinguish visual similarity amongst the species. The model was trained and evaluated on a dataset of 6,798 snake images from diverse sources. The system achieved a performance of 97% accuracy, 97% precision, 96% recall, an F1-score of 97%, and a ROC-AUC of 0.97. These results demonstrate that integrating CNN and LSTM is moderately effective for snake classification. The proposed system has practical applications in the area of emergency healthcare, wildlife management, as well as mobile based identification tool. With 97% accuracy, this model can improve emergency responders first aid, enhance a safer treatment administration and help make safer decisions on the use of antivenom, by reducing treatment delays and improving patient survival prognosis. This model has the potential to save lives and minimize the consequences of snakebite envenoming.